Finite-Time Boundedness of Switched Time-Varying Delay Systems with Actuator Saturation: Applications in Water Pollution Control - Shanmugam, Saravanan; Ali, M. Syed; Narayanan, G.; Rhaima, Mohamed (IEEE access, 2024)
This paper addresses the challenge of ensuring finite-time boundedness in switched time-varying delay systems with actuator saturation. Utilizing Lyapunov-Krasovskii functionals, we establish delay-dependent conditions through linear matrix inequalities, ensuring that switched systems with time-varying delays remain finite-time bounded. The paper also introduces the concept of average dwell time for switching signals, providing additional conditions for finite-time boundedness. Furthermore, the finite-time L 2 - L ∞ performance of switched systems with time-varying delays is investigated as a measure of disturbance capability within a finite-time interval. The estimator gain matrix can be determined by solving the linear matrix inequalities. The effectiveness of the proposed approach is illustrated through numerical examples.